HUBUNGAN ANTARA KONSEP DIRI DENGAN KEDISIPLINAN PESERTA DIDIK KELAS X MAN 1 PASAMAN - Munagi, Yuni; Zulkifli, Zulkifli; Kardo, Rici (Jurnal Manajemen Pendidikan, 2025)
This research was motivated by the existence of students coming to school late, quarrelling with their friends, not doing schoolwork, neglecting the regulations made by the school, and littering. This study aims to describe: 1) Student discipline, 2) Student self-concept, 3) Relationship between self-concept and student discipline. This study uses a descriptive quantitative method with a correlational approach, which aims to describe and analyze data, and determine the relationship between self-concept variables and the discipline of class X students at MAN 1 Pasaman. The sampling population using the total sampling of the entire population is 52 students in class X. The instrument used in this study is a questionnaire. The data analysis in this study is percentage and correlation. The results of this study show that 1) Students' discipline is in the high category.2) Students' self-concept is in the high category.3) And there is a significant relationship between discipline and students' self-concept (0.305) the hypothesis is accepted that there is discipline towards self-concept. Increase discipline in the aspect of obeying school rules. BK teachers on student discipline problems perform group services